A.P. Cowie (Editor). The Oxford History of English Lexicography. Volume I: General-purpose Dictionaries. Volume II: Specialized Dictionaries - Loránd-Levente Pálfi (Lexikos, 2011)
According to the blurb, The Oxford History of English Lexicography (volumes I–II) presents 'the fullest account yet published of the lexicography of English from its origins in medieval glosses, through its rapid development in the eighteenth century, to a fully-established high-tech industry that is as reliant as ever on learning and scholarship'. The term 'English lexicography' is interpreted broad-ly to embrace dictionaries not only of British English but also its national varie-ties such as Scots, American English, the varieties of English spoken in Aus-tralia, Canada, India, New Zealand, South Africa and the English-based Cre-oles of the Caribbean (cf. vol. I, p. 1). In addition, throughout the topical pres-entation numerous references are made to developments in Europe and else-where which have influenced the course of English lexicography.